Terms of the introduction of certain food products into the diet of children of the first year of life - Moiseeva, K.E.; Alekseeva, A.V.; Kharbediya, Sh.D; Gluschenko, V.A.; Sokolova, V.V.; Kirilenko, V.V (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2020)
To assess the terms of the introduction of certain foods in thediet of children of the first year of life-based on 5 Children’sClinics in St. Petersburg, an anonymous survey was conductedamong 534 mothers whose children received breastmilk up to a year and older. The study showed that in mostcases, mothers make their children drink water, tea, and juicein the first year of life in target dates. However, a significantnumber of mothers begin to introduce these liquids into thebaby’s diet earlier. The first complementary foods -fruit andvegetable puree- most of the children received timely (79.8%and 81.1%, respectively). The second complementary foods(cereal porridge) in 71.5% of cases were introduced in duetime and 24.5% - later than term. The third complementaryfoods (meat puree), as well as other protein products, whichinclude cottage cheese paste, egg yolk, and fish puree, childrenin most cases received later than term. 24.9% of mothersintroduced meat puree, 20.7% - cottage cheese paste,30.0% - egg yolk and 17.9% - fish puree earlier. Only 35.5%of mothers started to give fermented milk products on time,and 46.8% later. Whole milk in its natural form was receivedearlier than term by 61.4% of children. Thus, water, juice, tea,fruit and vegetable puree, as well as cereal was introducedinto the diet of the child in the recommended time, and meatpuree, cottage cheese paste, egg yolk, dairy products, fishpuree and whole milk later than the established period.